Learning for Food System Justice: Exploring Action Research and Knowledge Production in the Local Food Movement - Kim L. Niewolny (Adult Education Research Conference, 2013)
I explore how adult educators can contribute to food system justice through the lens of action research. The Applachian Foodshed Project provides a contemporary illustration of action research focusing on community food security. Implications emphasize food system movements as legitimate spaces for adult educational inquiry.